Methodology Of Modern Teachıng Dıdactıc Methods For Educatıon Of The Teacher Of Vocatıonal Educatıon Based On The Stratıfıed Approach - Safar Ruzıboev , Xoshımova Shoıra Safarovna (International Journal of Advanced Science and Technology, 2020)
The article explores the theoretical aspects of using modern teaching didactic tools in preparing a teacher of vocational education based on a differentiated approach, which is scientifically based on the need to make stratification in educational institutions and the purposeful and continuous formation of the knowledge and skills that students need. There is also a method for using modern teaching didactic tools in training based on a differentiated approach.